Empowering the Student as a Stakeholder; Through Incorporating Their Feedback in Modifying Curriculum of Oral Biology (Medical Forum Monthly, 2021)
Objective: To empower student as a stakeholder by incorporating their feedback in modifying curriculum of Oral Biology, which may be helpful for improving it.Study Design: Qualitative explorative studyPlace and Duration of Study: This study was conducted at the A qualitative explorative study was conducted during 6 month period, from Feb to Aug 2020 was done at Foundation University College of Dentistry(FUCD), Islamabad.Materials and Methods: Equally stratified students were involved in focus group discussion (FGD) in two session as per their academic accomplishments i.e. high highfliers (70-80%) and low fliers (56-62%) scores in Oral Biology. In both FGD session, 14 students participated.Results: Students expressed 6conjoint themes on which are the followings; i) Teaching mode, ii) Problems in First year BDS (Bachelor of Dental Surgery) education, iii) Teachers/Students cooperation, iv) Faculty qualification/ experience status ,v) Student’s role in curriculum development and vi) Lack of interactive sessions.Conclusion: Our study findings indicate that the curriculum status can be made better by integrating multiple teaching modes and by including feedback of student as a substantial source of analytical input. The weaknesses highlighted by the feedback of student’s regarding curriculum, syllabus, teachers and methods of evaluation are essential for high quality learning.